Pengaruh Gaya Mengajar Resipokal Terhadap Hasil Belajar Dribbling Permainan Sepak Bola Siswa Kelas VII SMP Negeri 8 Pagaralam - Jody Kurniawan; Sukardi Sukardi; Taheri Akhbar (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
In the situation of learning basic technical material for dribbling in the game of soccer in class VII of SMP Negeri 8 Paragalam, it was found that the majority of students had not completed the KKM, because conducting experiments by applying a reciprocal teaching style was expected to be a solution to this problem. This research aims to determine whether there is an influence of a reciprocal teaching style on the learning outcomes of dribbling soccer games for class VII students at SMA Negeri 8 Pagaralam. The method used is an experimental method with a one group pretest-posttest research design. The research population consisted of 30 students and samples were taken from a total population of 30 people. Data collection uses psychomotor skills sheets. Data analysis used SPSS paired sample t test. The research results stated that there was an influence of the reciprocal method on dribbling learning outcomes in class VII students at SMP Negeri 8 Pagaralam because tcount > ttable (10.926 > 1.69)